A man of Parliament : selected speeches from Joe Clark - Clark, Joe, 1939- (Queen's policy studies., 2019)
"An anthology of poignant and important speeches from Canada's sixteenth prime minister. Joe Clark--statesman, businessman, writer, and politician--served as the sixteenth prime minister of Canada from 4 June 1979 to 3 March 1980. Despite his relative inexperience, Clark rose quickly in federal politics, gaining a seat in the House of Commons in the 1972 election and winning the leadership of the Progressive Conservative Party only four years later. This volume collects a number of significant speeches from Joe Clark's illustrious career in Parliament. It captures over forty years of his public service from when he was a rookie member of Parliament, to his time as the prime minister, a cabinet minister, and the senior statesman of the House of Commons. His speeches are arranged in thematic areas such as parliamentary accountability, foreign affairs, constitutional debates, and the economy. Insightful and wide-ranging, A Man of Parliament demonstrates that Joe Clark's influence on Parliament continues to shape contemporary policy debates."--